Opieka psychologiczna w paradygmacie opieki paliatywnej w perinatologii nad rodzicami po potwierdzeniu wad letalnych u płodu/dziecka. Doświadczenia Ginekologiczno-Położniczego Szpitala Klinicznego Uniwersytetu Medycznego w Poznaniu - Łuczak-Wawrzyniak, Jadwiga; Borkowska-Kłos, Monika; Gruca-Stryjak, Karolina (Człowiek i Społeczeństwo, 2024)
The paper discusses the role of a clinical psychologist in the psychological care model within the interdisciplinary team dealing with perinatal palliative care at the Gynecological and Obstetrics Clinical Hospital of the Medical University of Poznań. In the context of the challenges of prenatal diagnosis, which provides information about the child’s health but also medicalizes the parents’ experiences, this work explores the psychological impact of receiving information about a fatal fetal/child defect on parents. Psychological interventions are analyzed for their impact on the decision-making process and the emotional state of parents, highlighting the need to include palliative care as a form of support for the family, beyond merely a medical procedure. The authors emphasize that accompanying parents while waiting for the birth of a child with lethal defects requires an interdisciplinary approach involving specialists from various fields, such as gynecology, perinatology, genetics, neonatology, and obstetrics, as exemplified by the Gynecological and Obstetrics Clinical Hospital, Medical University of Poznań. The work underscores that effective cooperation between the team and parents is rooted in the concept of assistance, characterized by openness and empathy, fostering emotional support and enabling parents to regain a sense of control and optimism. In conclusion, the article demonstrates how integrating medical knowledge and psychological practices in the context of perinatal palliative care can enhance understanding of parents’ needs and support them in navigating difficult decisions and emotions related to the diagnosis of a lethal fetal defect, thereby improving their parenting experience.